The mind of the customer : - Hodge, Richard. (McGraw-Hill, 2006)
The Mind of the Customer offers an in-depth analysis of today’s customers’ wants, needs, and problems, and reveals groundbreaking insights into the new expectations of today’s top sales executives. Drawing from their interviews with 96 high-level executives at corporations such as Lexus, Nokia, and UPS, The Real Learning Company’s Richard Hodge and Lou Schachter uncover what the new generation of salespeople needs to know to succeed--what clinches the deal, what loses it. The Mind of the Customer presents a four-pillared approach that defines a world-class sales force strategy: UNDERSTAND: Know what drives each business, what challenges the business faces, and what global and industry contexts the business operates within. CREATE: Appreciate what each customer really values. Pay attention to all the relevant dimensions of value and avoid solely price-driven interactions. COMMUNICATE: Make presentations interactive and negotiations cooperative. Create an atmosphere amenable to change and mutual success. MANAGE: Provide opportunities for salespeople to gain knowledge, develop new mindsets, and build skills. Focus on coaching and education.